Thermodynamic studies on tert-amine modified polystyrene based polymer/solvent systems by inverse gas chromatography method - Adiguzel, A. Cigdem; Korkmaz, Burak; Cakar, Fatih; Cankurtaran, Oziem; Senkal, B. Filiz (YILDIZ TECHNICAL UNIV, 2021)
In the present work, vinyl benzyl chloride (VBC) was polymerized by using free radical polymerization. The obtained PVBC was reacted with dibutyl amine to obtain tertiary amine modified polystyrene based polymer (PVBC-Dibutyl amine). The inverse gas chromatography (IGC) method was used to examine the thermodynamic properties of the polymer. Firstly, the retention diagrams of some polar and non-polar solvents on PVBC-Dibutyl amine were obtained over a temperature range from 135 to 160 degrees C. Then, the thermodynamic parameters, including Flory-Huggins interaction parameter, weight fraction activity coefficient, partial molar heat of sorption, and partial molar heat of mixing were determined via interactions between the polymer and selected solvents at infinite dilution. The results reveal that the alkanes are poor solvents for the polymer whereas n-butyl acetate, i-butyl acetate, ethyl acetate, n-propylbenzene, i-propylbenzene, and ethylbenzene are moderately solvents in the studied temperature range.
Keywords: Inverse gas chromatography; Thermodynamics; Polystyrene based polymer; POLYMERS; INFINITE; Engineering